A Randomized, Double-Blind Clinical Study on the Safety and Tolerability of an Iron Multi-Amino Acid Chelate Preparation in Premenopausal Women. (8th February 2013) - Fouad, Gameil T.; Evans, Malkanthi; Sharma, Prachi; Baisley, Joshua; Crowley, David; Guthrie, Najla
ABSTRACT Considerable risk of iron deficiency has been identified in premenopausal women because of the adverse effects associated with commercial iron preparations. This study examined the safety and tolerability of a novel iron multi-amino acid chelate (IMAAC) preparation in premenopausal women. A single-centre, randomized, double-blind, three-arm placebo-controlled (n = 60) study was conducted where subjects received one of three test materials: IMAAC (600 mg) or ferrous sulfate (600 mg) each containing 25 mg of elemental iron, or placebo as a single daily dose for 7 days. After testing, there were no significant differences found in any of the hematological outcomes between the different test groups. The safety analyses showed that a significantly (p = .044) higher number of patients reported adverse events when taking the ferrous sulfate supplement compared to IMAAC. A significantly lower number of adverse effects (p = .008) were reported by subjects on IMAAC. The current study demonstrated the superiority of the IMAAC preparation over ferrous sulfate with regards to tolerability and adverse effects.